Profile of Antihypertensive Therapy Use in Patients with Ischemic Stroke at a Type C Hospital Jember Regency - Nanda Yulita Sari; Nafisah Isnawati (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2026)
Abstract Background: Ischemic stroke is a condition resulting from obstructed blood flow to the brain, with hypertension serving as a comorbid risk factor. Controlling hypertension in ischemic stroke patients is a crucial aspect of management for preventing clinical deterioration and supporting the recovery process. Therefore, a study on the antihypertensive medication usage profile in ischemic stroke patients is necessary to serve as a basis for evaluating and improving the quality of therapy provided. Purpose: This study aimed to determine the profile of antihypertensive drug use among ischemic stroke patients at a Type C hospital in Jember Regency. Methods: This study employed a descriptive observational design with a retrospective approach, utilizing medical record data from ischemic stroke patients undergoing antihypertensive therapy at a Type C hospital in Jember Regency. The study sample consisted of 30 patients who met the inclusion criteria. The variables examined included patient characteristics and patterns of antihypertensive therapy use. Data analysis was conducted descriptively, and the results are presented as frequency distributions and percentages. Results: The majority of patients were male (84%) and fell within the 56–59 age group (36.7%). The most frequently used class of antihypertensive drugs was Angiotensin Receptor Blockers (ARBs); specifically, candesartan 8 mg was used in 13 patients (43.3%) and valsartan 80 mg in 8 patients (26.7%). Within the Calcium Channel Blocker (CCB) class, amlodipine 10 mg was used in 13 patients (43.3%). Additionally, diuretic usage included furosemide 20 mg in 9 patients (30.0%) and spironolactone 100 mg in 8 patients (26.7%), while ramipril 5 mg—representing the Angiotensin-Converting Enzyme Inhibitor (ACEI) class—was used in 9 patients (30.0%). Conclusions: The most commonly used antihypertensive drugs for ischemic stroke patients at the Type C hospital in Jember Regency belonged to the ARB and CCB classes.